2017
DOI: 10.1093/jnci/djx042
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Radiotherapy for Patients with Early-Stage Glottic Cancer: Patterns of Care and Survival

Abstract: HFX is associated with improved survival compared with CFX among patients treated with definitive radiotherapy for ESGC, particularly among patients with cT2 disease. HFX utilization increased over the study period; however, 40% of patients in our cohort did not receive HFX in the most recent year of our analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 20 publications
1
19
1
Order By: Relevance
“…Consequently, hypofractionation has gained favor in recent years because this schedule is more advantageous for both patients and staff. Therefore, the use of hyperfractionation and CF at our Institution have been decreasing over the past few years (Figure 1), which is consistent with a study in the United States that showed increased use of hypofractionation for EGSCC over the years, with more than half of patients choosing it recently (10,23). Moore et al and consensus guidelines strongly recommend hypofractionation as the standard of care.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, hypofractionation has gained favor in recent years because this schedule is more advantageous for both patients and staff. Therefore, the use of hyperfractionation and CF at our Institution have been decreasing over the past few years (Figure 1), which is consistent with a study in the United States that showed increased use of hypofractionation for EGSCC over the years, with more than half of patients choosing it recently (10,23). Moore et al and consensus guidelines strongly recommend hypofractionation as the standard of care.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, the high patient numbers in the NCDB facilitate the detection of small differences in survival associated with different radiotherapy techniques. To this end, using the NCDB, we and others observed survival differences in patients treated with different fraction sizes which were not observed in the original randomized trials addressing this issue [22,[24][25][26]. Although the impact of IMRT on local control and toxicity is unknown, we did not find any difference in OS between IMRT and 3DCRT.…”
Section: Discussioncontrasting
confidence: 47%
“…Trevor et al. in the group of 10,212 patients with T1 glottic cancer noted a 2.2% improvement in 5‑year OS after hypofractionated radiotherapy [41]. Ermis et al.…”
Section: Discussionmentioning
confidence: 99%